Keefektifan Blended - Problem Based Learning terhadap Pemecahan Masalah pada Materi Ekologi - Elok Dyah Pitaloka; Slamet Suyanto (Graduate School of Universitas Negeri Malang, 2019)
Abstract: Biology learning must utilize technology and direct students to have problem solving skills, so that learning innovations are blended-problem based learning. This study aims to look at the effectiveness of blended-problem based learning on problem solving, when compared to learning that applies the scientific approach (5M). This study categorized as quasi-experimental research, using the design of the pretest-posttest control group. The independent t-test obtained the sig value. 0.00 <0.05, so that it can be interpreted that the posttest value of the executive class and control is significantly different. N-Gain score testing was obtained from the 0.70 high category experimental class, while 0.298 for the low category control class. Based on these data, blended-problem based learning can be said to be effective against solving ecological chapter problems.Abstrak: Pembelajaran Biologi harus memanfaatkan teknologi dan mengarahkan peserta didik memiliki kemampuan pemecahan masalah sehingga memunculkan inovasi pembelajaran blended-problem based learning. Penelitian ini bertujuan melihat keefektifan blended-problem based learning pada pemecahan masalah, jika dibandingkan pembelajaran yang menerapkan pendekatan saintifik (5M). Penelitian ini dikategorikan penelitian eksperimen semu menggunakan desain pretest-posttest control group. Uji independent t-test memperoleh nilai sig. 0,00<0,05, sehingga dapat diartikan nilai posttest kelas ekseprimen dan kontrol berbeda signinifikan. Pengujian N-Gain score diperoleh reratal kelas ekspeimen 0,70 kategori tinggi, sedangkan 0,298 untuk kelas kontrol kategori rendah. Berdasarkan data tersebut, blended-problem based learning dapat dikatakan efektif terhadap pemecahan masalah bab ekologi.